Towards a participatory approach to Bible translation (PABT) - Chemorion, D. C. (Acta Theologica, 2009)
It is generally acknowledged that the participation of the receptor community may enhance the community’s ownership and acceptability of the translation. In spite of this acknowledgement, individuals and organisations engaged in mother tongue translations of the Bible often involve the members of the receptor community in secondary and non-technical aspects of the translation process. Crucial decisions regarding the nature of the translation are often made by the translation team without adequate input from the community. Part of the reason for non-involvement of the receptor communities in the technical aspects of Bible translation has been the lack of an adequate theoretical framework that explains how the community may fit in the translation process. On the basis of Christiane Nord’s functionalist model of translation, this article proposes a “Participatory approach to Bible Translation (PABT)” as a strategy that can be applied to involve the receptor community in technical aspects of the translation.